Functional and technological properties of frozen dough-based semi-finished products and cryopreservation of finished bakery products - Korniienko, Iryna; Huliaiev , Vitalii; Anatskyi, Andrii; Neposhyvailenko, Nataliia; Monchenko, Olena; Larycheva, Liudmyla; Filimonenko, Olha (Problems of Environmental Biotechnology, 2021)
The expediency of using cryoprotectants in the practice of production of functional bakery products is substantiated. Experiments have proved the effectiveness of the use of lactulose and oilseed meal, which makes it possible to increase the biological activity of the fermenting microflora at the level of 98% after thawing the dough pieces.